2009
DOI: 10.1021/ja9023644
|View full text |Cite
|
Sign up to set email alerts
|

Which One Is Preferred: Myers−Saito Cyclization of Ene-Yne-Allene or Garratt−Braverman Cyclization of Conjugated Bisallenic Sulfone? A Theoretical and Experimental Study

Abstract: A competitive scenario between Myers-Saito (MS) and Garratt-Braverman (GB) cyclization has been created in a molecule. High-level computations indicate a preference for GB over MS cyclization. The activation energies for the rate-determining steps of the GB and MS cyclizations were found to be the same (24.4 kcal/mol) at the B3LYP/6-31G* level of theory; thus, from the kinetic point of view, both reactions are feasible. However, the main biradical intermediate GB2 of the GB reaction is 6.2 kcal/mol lower in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…The results demonstrated that both sulfones have cleavage activity ( Figure 2). Although the cleavage efficiency of the aromatic sulfone 7 did not improve much, the aliphatic sulfone 8 showed much stronger DNA-cleaving activity (72 % at 20 mm relative to 10 % at 1 mm for acyclic sulfones as already reported [11] ).…”
Section: Experimental Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…The results demonstrated that both sulfones have cleavage activity ( Figure 2). Although the cleavage efficiency of the aromatic sulfone 7 did not improve much, the aliphatic sulfone 8 showed much stronger DNA-cleaving activity (72 % at 20 mm relative to 10 % at 1 mm for acyclic sulfones as already reported [11] ).…”
Section: Experimental Studiessupporting
confidence: 68%
“…Semmelhack et al [18] had previously reported the formation of a product that arose out of similar trapping with a phenyl radical. Now that we were able to switch the preference from GB to SCM or MS, these sulfones were expected to show better DNA-cleavage activity than that for earlier reported [11] similar compounds that undergo GB cyclization. Thus the sulfones 7 and 8 were incubated with pBR322 DNA at pH 8.5.…”
Section: Experimental Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…One example 62 is the controversy regarding the involvement of a monoallene or bis-allene during Garratt-Braverman cyclization of bis-propargyl ether or sulfone. 63,64 The allenes from bis-naphthyl ether and sulfone were trapped with methanol, and the reaction mixture was subjected to LALDI-MS. The bis-naphthyl system was chosen for this study because the naphthyl moiety can act as a label capable of absorbing the laser light.…”
Section: Use Of Amidopyrene To Study Protein-ligand Bindingmentioning
confidence: 55%
“…It has been observed that the emission of TNP treated cells are quenched ( Figure 5) which is in line with the experimentation. The outcome indicates that the chemosensor Br-LANS prepared by Garratt-Braverman cyclization [45] could be useful as biocompatible chemosensor for detection of TNP like lethal environment pollutant.…”
Section: Intracellular Detection Of Tnp Like Nacs: a Real Day Applicamentioning
confidence: 96%